Effect of Disinfection Technique of Spraying and Soaking Peronema canescens Jack 1% on Changes in Alginate Dimensions - Fadriyanti, Okmes; Widyawati, Widyawati; Marwi, Hamna (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Alginate prints can be a medium of transmission that has the potential for cross-infection. Prevention of cross-infection can be done by spraying and soaking disinfection. Alginate molds in contact with water can cause the material to expand. Sungkai leaves (Peronema canescens jack) which contain antibacterials, can be a disinfection agent. Objective: This research is to determine the effect of spraying and soaking disinfection techniques with 1% sungkai leaf extract on changes in the dimensions of alginate molds. Methods: Making alginate mold samples totaling 72 samples, consisting of 6 groups and measured within 5, 10, 15 minutes. Test changes in dimensions of the alginate mold using digital calipers were analyzed using the Wilcoxon test followed by the Mann-Whitney test. Results: there was no effect of spraying with 1% sungkai leaf extract (Peronema canescens jack) on changes in the dimensions of the alginate mold within 10 minutes (p0.05), and there was an effect of soaking within 10 minutes on the dimensions of the alginate mold. Conclusion: disinfection by spraying and soaking with 1% sungkai leaf extract against changes in the dimensions of the alginate mold still complies with ADA specifications at the clinical tolerance limit below 0.5%.